On cloused ideals of entire functions of finite gamma-growth - Malyutin, K. G.; Gerasimenko, V. O. (Methods of Functional Analysis and Topology, 2007)
We extend the result of Beurling on the closure in H^p of the linear manifold F(z)· {polynomials of z} to the classes of entire functions of finite gamma-growth.